Monitoring of semi-permanent troughs and ridges in relation to monsoon - ASNANI , G. C.; AWADE, S.T. (MAUSAM, 1978)
Two contrasting years (1967 and 1972) have been selected for intensive study in respect of large scale features of northern hemispheric contour field. In the present study, 700 and 300 mb mean monthly contours at different latitude circles at 5 degree interval, were subjected to Fourier analysis and horizontal and vertical tilts of troughs and ridges determined. At and north of 20°N, under quasi-geostrophic assumption, computations have been made to calculate meridional transports of momentum by tilted troughs and ridge at 700 and 300 mb levels and meridional transport of sensible heat at 500 mb level. The following chief results have been obtained. (i) The differences in momentum transport during the two contrasting years were far more marked at 300 mb level than at 700 mb level. (ii) In a year of good monsoon (1967), there was an anomaly of northward transport of momentum across sub-tropical latitudes while in a year of poor monsoon (1972), there was anomaly of southward transport of momentum across the subtropical latitudes, at 300 mb level. (iii) During a year of good monsoon (1967), there was anomaly of southward transport of sensible heat across the sub-tropical latitude of 30°N at 500 mb level, while in a year of poor monsoon (1972), the anomaly was in the form of northward transport. (iv) The anomalies in the transports of momentum and sensible heat during 1967 and 1972 were perceptible about a month before the onset of monsoon over India. If this be true also for other years which have not been studied here, then there is a possibility of foreshadowing large-scale behaviour of the Indian monsoon one month or so ahead of the arrival of the monsoon. (v) In terms of the anomalies in meridional transports or momentum and sensible heat across the sub-tropical latitudes, we present a model of abnormal monsoon in India. If the summer tropical atmosphere is warmer (cooler) than normal, the monsoon rainfall over India is likely to be more (less) than normal. This is shown to be in broad agreement with what is presently known about the theory of monsoon and observations of short-period anomalies in the behaviour of the Indian monsoon.